2016
DOI: 10.1038/ncomms13723
|View full text |Cite
|
Sign up to set email alerts
|

Stability of peatland carbon to rising temperatures

Abstract: Peatlands contain one-third of soil carbon (C), mostly buried in deep, saturated anoxic zones (catotelm). The response of catotelm C to climate forcing is uncertain, because prior experiments have focused on surface warming. We show that deep peat heating of a 2 m-thick peat column results in an exponential increase in CH4 emissions. However, this response is due solely to surface processes and not degradation of catotelm peat. Incubations show that only the top 20–30 cm of peat from experimental plots have hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
186
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(224 citation statements)
references
References 63 publications
35
186
2
1
Order By: Relevance
“…The decrease in the pore water DOC below 50 cm was not consistent with the slow decomposition (and increased humification) observed in the solid peat with depth at the same site (Tfaily et al, ), consistent with the idea that microbial communites at the S1 bog are preferentially utlizing DOC deep in the peat column. These observations support radiocarbon measurements in Tfaily et al () and Wilson et al (), where radiocarbon signatures of microbial respiration products in deeper catotelm static zone resembled those of DOC rather than solid peat, indicating that carbon derived from recent photosynthesis and peat in upper layer fuels the bulk of the decomposition at depth, even in the catotelm. Since the bulk of the respiration products (dissolved CO 2 and CH 4 ) within the peat column resemble the DOC, and that DOC at depth has a surface derived 14 C signature (Tfaily et al, ; Wilson et al, ), the rate of microbial respiration within the peat column at S1 bog is suggested to be greater than the rate of solid phase peat decomposition (Tfaily et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The decrease in the pore water DOC below 50 cm was not consistent with the slow decomposition (and increased humification) observed in the solid peat with depth at the same site (Tfaily et al, ), consistent with the idea that microbial communites at the S1 bog are preferentially utlizing DOC deep in the peat column. These observations support radiocarbon measurements in Tfaily et al () and Wilson et al (), where radiocarbon signatures of microbial respiration products in deeper catotelm static zone resembled those of DOC rather than solid peat, indicating that carbon derived from recent photosynthesis and peat in upper layer fuels the bulk of the decomposition at depth, even in the catotelm. Since the bulk of the respiration products (dissolved CO 2 and CH 4 ) within the peat column resemble the DOC, and that DOC at depth has a surface derived 14 C signature (Tfaily et al, ; Wilson et al, ), the rate of microbial respiration within the peat column at S1 bog is suggested to be greater than the rate of solid phase peat decomposition (Tfaily et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The earliest pretreatment measurements began in 2010 but several other measurements were initiated in later years. In 2014, a deep peat heating experiment (heating targeted at 2-m peat depth) was initiated (Wilson et al, 2016;Hanson et al, 2017), and thus pretreatment measurements of depth-specific peat characteristics were collected only until 2013. However, pretreatment measurements for shallow peat or aboveground processes were collected throughout the deep peat heating period and until whole-ecosystem warming commenced in August 2015.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Even if there is no relationship between a pretreatment variable and the assigned temperature differentials, spatial variation in ecosystem processes determined during the pretreatment period should be taken into account when analyzing post-treatment effects. Multiple statistical approaches can be used, including examining the relative deviation in a given measurement between the pretreatment and post-treatment period (e.g., the analysis of TOC concentrations in Wilson et al, 2016), using before-after, control-impact (Stewart-Oaten et al, 1986), and related analyses (Underwood, 1994), randomized intervention analysis (Carpenter et al, 1989) or various time series analysis approaches (e.g., Cazelles et al, 2008;Box et al, 2016).…”
Section: Concluding Remarks: Implications Of Spatial and Temporal Varmentioning
confidence: 99%
See 1 more Smart Citation
“…from studies conducted at single-marsh to regional scales are not conclusive either, ranging from no or small (Charles & Dukes, 2009;Kirwan et al, 2014;Janousek et al, 2017) to strong seasonallydriven temperature effects with a Q10 >3.4 as found within a single site (Kirwan & Blum, 2011). Wilson et al, 2016), temperature sensitivity of the used TBI materials was sufficiently demonstrated (Keuskamp et al, 2013). We therefore conclude that other parameters exerted overriding influence on k, mainly masking temperature effects and have not been captured by our experimental design.…”
Section: Temperature Effects On Decomposition Processesmentioning
confidence: 72%